Bay trees, Trinidad - (:unkn) unknown (Davidson and Todd Ltd., Trinidad, 2010)
Bay trees create a shaded canopy.
Colour: Sepia; Style: Portrait; Other; Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Trees--Trinidad and Tobago; Rural roads--Trinidad and Tobago; Bay (Tree)